Statement by the Managing Director on the Independent Evaluation Office Report on Governance of the IMF. (Policy Papers; Policy Paper ;, 2018)
I would like to thank the Independent Evaluation Office (IEO) for preparing this informative update on the 2008 report on governance of the IMF. It is reassuring that the Update recognizes the significant progress made in improving efficiency, accountability, and voice of the Fund's main governance bodies, and I concur that the remaining challenges need our continued attention and collective commitment.